Lifetime medical expenditure and life expectancy lost attributable to smoking through major smoking related diseases in Taiwan - Chung, Chih‐Wen (BMJ Group, 2007)
OBJECTIVE: To estimate the lifetime financial burden on Taiwan's national health insurance (NHI) system, life expectancy and years of life expectancy lost (YLEL) attributable to smoking from major smoking related diseases. METHODS: 10 major smoking related diseases (seven cancers, stroke, acute myocardial infarction and chronic obstructive pulmonary disease) were selected for this study. A survival analysis was conducted on linked cohorts from the National Death Registry database and the National Cancer Registry (NCR) and patients at the National Taiwan University Hospital (NTUH). Estimation of the smoking attributable fraction (SAF) for the study diseases was undertaken by combining the relative risks of smokers against non‐smokers and the prevalence of smoking in Taiwan. The YLEL attributable to smoking was calculated for the study diseases by combining the survival analysis results, the SAF and the annual incidences of each disease. The lifetime medical expenditure for the study diseases was estimated by integrating the survival curve and the mean annual medical costs calculated from NHI reimbursement records. RESULTS: There were 241 280 incidents of the 10 study diseases in 2001, of which about 53 648 cases (22.2%) were attributable to smoking, with a total YLEL of 191 313 at an average of about 3.6 YLEL per case. For each case, the average survival time was about 10.2 years. Under two different annual discount rates, the total lifetime financial burden on the NHI was estimated at between $291 million (£147 million; €216 million) (3% discount) and $336 million (1% discount) for all diseases attributable to smoking in 2001, accounting for about 24.6% of the total estimated lifetime medical expenditure for all incidents of the 10 study diseases. CONCLUSIONS: Smoking places tremendous financial and health burdens upon both society and individuals. A much more stringent tobacco control strategy is needed to curb the damage from smoking.